International responsibility for damage caused by cyber attacks - محمود لمى عبدالباقي; كيطان اسراء نادر (Journal of Legal Sciences, 2021)
The research sheds light on a new topic of international law, the most important of which is, around which there are still question marks and differences in most of its aspects, especially with regard to international liability for damage caused by cyber attacks in the virtual space, the last is the fifth area that appeared alongside other area (Land, sea, air and outer space) and in addition to being a space on which states depend in the performance of their functions and international relations, it is a new arena for war and a source of danger to the security of states, As the security exposure to the secrets of states increased due to espionage and piracy, and the attacks on the infrastructure of countries increased, and the silence of states at times and the difficulty in knowing the attacker or the attributing the act to a specific country or party led to an exacerbation of the problem that may turn from a mere attack to a war on the ground, Therefore, the problem of concealing the identity of the attacker must be overcome and the international liability system must be activated in this space because it is the basis of the international legal system. Through its activation, it is possible to confront the dangers and preserve cyber security, which has become an important issue in our time.